(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
This paper aims to present the main aspects inherent in the scenic composition of the play Erêndira, staged at the Municipal Market of the City of Belo Horizonte, in order to highlight aspects of intersection between the scenic characterization of the character Erêndira and the scenographic devices present in the Visual Stations manufactured for the staging of the play. In general, I intend to elucidate the principles that encompassed the idea of composition of the costumes of the main character and the way in which they were put together with the scenographic creation of the Visual Stations of the performance.